A numerical algorithm to find a root of non-linearequations using householder’s method - Srinivasarao Thota (International Journal of Advances in Applied Sciences, 2021)
In this paper, we propose a three step algorithm using Householder’s method for find-ing an approximate root of the given non-linear equations in one variable. Severalnumerical examples are presented to illustrate and validation of the proposed method.Implementation of the proposed algorithm in Maple is also discussed with samplecomputations.